HYPOTHYROIDISM IN THE EXPERIMENTAL MODEL OF ALZHEIMER - Lenara Serverovna Seit-Asan (European Science Publishing, 2024)
Thyroid hormones (TG) have a wide and important range of effects in the central nervous system. Thyroid diseases are one of the main causes of cognitive impairment, including Alzheimer's disease (AD). The aim of this work was to study individual indicators of thyroid hormones in an experimental model of a neurodegenerative state with symptoms of Alzheimer's disease (MA)
Keywords: Alzheimer's disease, thyroid hormones, thyroid gland, hypothyroidism.